2016
DOI: 10.5935/0103-5053.20160191
|View full text |Cite
|
Sign up to set email alerts
|

MALDI Imaging Mass Spectrometry of Fresh Water Cyanobacteria: Spatial Distribution of Toxins and Other Metabolites

Abstract: Cyanobacteria are among the most ancient forms of life, yet they are known to synthesize highly sophisticated defense molecules, such as the highly hepatotoxic cyclic peptides microcystins and nodularins produced by the genera Microcystis, Anabaena and Nodularia. These metabolites are released by cyanobacteria to water environments causing episodes of fatalities among animals and humans. To better understand the releasing of these metabolites, imaging mass spectrometry (IMS) using matrix-assisted laser desorpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Imaging mass spectrometry (IMS) by matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) has been used to evaluate the spatial distribution of cyanobacterial siderophores colonies grown on agar [118]. This technique may open a window for exploring siderophore cycling within complex biofilms in the future.…”
Section: Identification Methodsmentioning
confidence: 99%
“…Imaging mass spectrometry (IMS) by matrix-assisted laser desorption ionization-time of flight (MALDI-TOF) has been used to evaluate the spatial distribution of cyanobacterial siderophores colonies grown on agar [118]. This technique may open a window for exploring siderophore cycling within complex biofilms in the future.…”
Section: Identification Methodsmentioning
confidence: 99%
“…Cyanopeptides such as aeroguniosins, microcystins and cyanopeptolin were also detected. The morphological research showed that the bulk of the population of cyanobacteria belonged to the genus Microcystis [46].…”
Section: Occurrencementioning
confidence: 99%
“…The technique allowed studying the distribution of molecules in tissue sections covered with an organic matrix, which absorbs the light from a pulsed laser and supports efficient ionization of peptides and other biomolecules. MALDI-MS has been used previously for the analyses of MCs in water, and MALDI-MSI was used to analyze MCs in cyanobacterial colonies [21,22].…”
Section: Introductionmentioning
confidence: 99%